Traditional and modern foods - Balogh Sándor (Agrár- és vidékfejlesztési szemle, 2011)
The lecture aims to present the “family tree” which shows the “phylogeny“ of foods and which demonstrates that the process of product development in food industry shows a certain, largely predictable regularity.